2023
DOI: 10.1002/ece3.10198
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile survival and movements of two threatened oceanic sharks in the North Atlantic Ocean inferred from tag‐recovery data

Abstract: Understanding population dynamics, movements, and fishing mortality is critical to establish effective shark conservation measures across international boundaries in the ocean. There are few survival and dispersal estimates of juveniles of oceanic shark species in the North Atlantic despite it being one of the most fished regions in the world. Here we provide estimates of dispersal, survival, and proportion of fishing mortality in the North Atlantic for two threatened oceanic sharks: the blue shark (Prionace g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…If there are exchanges, they are also mainly in the ‘Atlantic to Mediterranean’ direction as the number of haplotypes specific to the Mediterranean was important and was not found in the Atlantic. This is consistent with the tagging studies of blue sharks that, despite a low recapture rate, have shown no evidence of blue shark migration between the Atlantic and the Mediterranean [ 57 – 61 ]. Other pelagic or migratory fishes also exhibit genetic differentiation between Atlantic and Mediterranean populations at microsatellite and mtDNA loci, such as the meagre ( Argyrosomus regius ) [ 62 ] and the strait of Gibraltar serves as a barrier to gene flow for many species regardless of their spatial ecology [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If there are exchanges, they are also mainly in the ‘Atlantic to Mediterranean’ direction as the number of haplotypes specific to the Mediterranean was important and was not found in the Atlantic. This is consistent with the tagging studies of blue sharks that, despite a low recapture rate, have shown no evidence of blue shark migration between the Atlantic and the Mediterranean [ 57 – 61 ]. Other pelagic or migratory fishes also exhibit genetic differentiation between Atlantic and Mediterranean populations at microsatellite and mtDNA loci, such as the meagre ( Argyrosomus regius ) [ 62 ] and the strait of Gibraltar serves as a barrier to gene flow for many species regardless of their spatial ecology [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study supports the distinction of two genetic stocks for the blue shark in the Mediterranean Sea and Atlantic Ocean. Recent important tagging and tracking efforts both in the Atlantic [ 61 ] and the Mediterranean Sea [ 60 ] also support a lack of connection between the two basins. Thus, the precautionary principle applied by the ICCAT and consisting of separating these basins for management purposes is appropriate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…When achievable, total annual mortality ( A ) should ideally be estimated from capture‐mark‐recapture (CMR) studies (Bradshaw et al ., 2007; Caza‐Allard et al ., 2021) in which apparent total annual survival ( S ) is obtained, and therefore also A = 1− S . This is because such an approach can sometimes discriminate mortality from other different demographic processes (i.e., emigration) and even further partition this life‐history trait into its natural ( M ) and fishing ( F ) components (Lees et al ., 2021; Mucientes et al ., 2023). As a less resource‐demanding alternative, the age‐frequency data of randomly sampled fish may be used instead to estimate the instantaneous mortality ( Z ) that reflects the additive but indistinguishable effects of M and F , and from which A can then be obtained (Allen & Hightower, 2010; Miranda & Bettoli, 2007; Ogle, 2016; Pauly, 1984; Simpfendorfer et al ., 2005).…”
Section: The Contextmentioning
confidence: 99%